Sustainability management accounting and organizational performance: the mediating role of environmental management system - Mohd Fuzi, Nursyazwani; Ramdan, Mohamad Rohieszan; Yong, Sharon Yee Ong; Osman, Juliana; Kolandan, Subramaniam; Mohd Ariffin, Siti Zubaidah; Jamaluddin, Nor Sa’adah; Abdullah, Karmilah (Multidisciplinary Digital Publishing Institute, 2022)
The aim of this study was to investigate the relationship between sustainability management accounting, environmental management system, and organizational performance for the Malaysian manufacturing industry. The data were collected from 350 manufacturing companies in Malaysia using online questionnaires. Structural equation modeling was used to investigate the relationship between sustainability management accounting, environmental management system, and organizational performance. The findings showed that there was a significant positive relationship between sustainability management accounting and organizational performance (β = 0.530, p < 0.001), sustainability management accounting and environmental management system (β = 0.583, p < 0.001), and environmental management system and organizational performance (β = 0.168, p < 0.05). The findings also found an indirect effect of sustainability management accounting on organizational performance (β = 0.271, p < 0.05) through environmental management system implementation. Results show that environmental management systems can be considered as partial mediators. The environmental management system as a mediator for the Malaysian manufacturing industry increased the impact of sustainability management accounting on organizational performance. This study provides a fundamental approach for practitioners and manufacturing researchers to improve organizational performance through the implementation of sustainability management accounting and environmental management systems.